Refinement of Surface Mesh for Accurate Multi-View Reconstruction - Tyle_ek, Radim; Šára, Radim (International Journal of Virtual Reality, 2010)
In this paper we propose a pipeline for accurate 3D reconstruction from multiple images that deals with some of the possible sources of inaccuracy present in the input data. Namely, we address the problem of inaccurate camera calibration by including a method adjusting the camera parameters in a global structure-and-motion problem, which is solved with a depth map for representation that is suitable to large scenes. Secondly, we take the triangular mesh and calibration improved by the global method in the first phase to refine the surface both geometrically and radiometrically. Here we propose surface energy which combines photoconsistency with contour matching and minimize it with a gradient descent method. Our main contribution lies in effective computation of the gradient that naturally regularization and data terms by employing scale space approach. The results are demonstrated on standard high-resolution datasets and a complex outdoor scene.